Deletion mapping and heterogenote analysis of a mutation responsible for osmosis-sensitive growth, spectinomycin resistance, and alteration of cytoplasmic membrane in Escherichia coli. - Yamagata, H (1980)
Lambda transducing phages carrying Escherichia coli deoxyribonucleic acid of various lengths from the aroE-rpsL region were lysogenized into the F'3 plasmid and were used for heterogenote analysis of YM101, a sucrose-dependent, spectinomycin-resistant mutant of E. coli. Three characteristics of the mutant strain, resistance to spectinomycin, sucrose dependence of growth, and lack of I-19 protein in the cytoplasmic membrane, were shown to be the result of a mutation in a region designated delta 53-spcl. This region extends over 3.6-kilobase pairs and is located within a cluster of ribosomal genes. The mutation is recessive to the wild-type allele.